2018
DOI: 10.1186/s13287-018-0780-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in the osteosarcoma microenvironment: their biological properties, influence on tumor growth, and therapeutic implications

Abstract: During tumorigenesis and development, participation of the tumor microenvironment is not negligible. As an important component in the tumor microenvironment, mesenchymal stem cells (MSCs) have been corroborated to mediate proliferation, metastasis, and drug resistance in many cancers, including osteosarcoma. What’s more, because of tumor site tropism, MSCs can be engineered to be loaded with therapeutic agents so that drugs can be precisely delivered to tumor lesions. In this review, we mainly discuss recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 57 publications
0
76
0
Order By: Relevance
“…The action of INF-γ, TNF-α and IL-1α strengthen the growth-promoting effects of MSCs, while INF-γ, TNF-α and TGF-β enhance the ability of MSCs to promote tumor metastases. In addition, MSCs may differentiate into associated fibroblasts to cancer under the stimulation of TGF-β (9).…”
Section: Introductionmentioning
confidence: 99%
“…The action of INF-γ, TNF-α and IL-1α strengthen the growth-promoting effects of MSCs, while INF-γ, TNF-α and TGF-β enhance the ability of MSCs to promote tumor metastases. In addition, MSCs may differentiate into associated fibroblasts to cancer under the stimulation of TGF-β (9).…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are especially known for their secretion of paracrine factors, which have beneficial effects on angiogenesis, cell survival, and restraining inflammation. 25,41,44,45 The encouraging results of opal substrate-based MSC transplantation on AMI mice in this study, as identified by decreased apoptosis of cardiomyocytes and a significant decrease of LV remodeling, are mainly due to this novel method. The secretion effects of MSCs were extremely encouraging, as shown by increased levels of SDF-1, Ang-1, and VEGF-α.…”
Section: Discussionmentioning
confidence: 72%
“…Consequently, MSCs have autocrine and paracrine trophic properties, as their secreted growth factors stimulate cell division and differentiation of MSCs, osteoblasts, and endothelial cells [62]. Furthermore, MSCs also secrete chemokines (C-C motif) ligand 5 (CCL5), stromal derived factor 1 SDF-1 or (C-X-C motif) chemokine 12 CXCL12, interleukin 6 (IL-6), and growth factor vascular endothelial growth factor (VEGF), known, among others, to promote OS growth, metastasis spread, and angiogenesis (reviewed in Reference [63]).…”
Section: Mscs As Sensors and Modulators Of Os Microenvironmentmentioning
confidence: 99%